PENGARUH JARINGAN USAHA, INOVASI PRODUK DAN PERSAINGAN USAHA TERHADAP PERKEMBANGAN USAHA MIKRO, KECIL DAN MENENGAH (Studi pada IKM Makanan di Kecamatan Kuningan Kabupaten Kuningan Jawa Barat) - Lestari, Citra; Lubis, Nawazirul; Widayanto, Widayanto (Jurnal Ilmu Administrasi Bisnis, 2015)
The development of a business unit can be affected by a variety of factors, both internal and external company factors. The purpose of this research is to know the influence of the business network, product innovation and competition against the development of micro, small and medium enterprises. The research type is explanatory research. The population was 562 units from small and medium food industries in Kuningan District with 85 sample taken using disproportionate stratified random sampling and simple random sampling. Data collection using the questionnaire. Data analysis using linear regression analysis. The results showed that the business network, product innovation and competition are jointly undertaking a positive and significant effect against involving the development of micro, small and medium enterprises. Researchers suggest that IKM constantly enhance cooperation with various parties to build wider business network, improve product innovation and improve competitiveness so that IKM can continue to thrive in the midst of the current competition.